The Potency of Camellia Sinensis L. to Reduce Proinflammatory Cytokine Levels in the Acute Respiratory Distress Syndrome Rat Model - Wahyu Widowati; Didik Priyandoko; Hanna Sari Widya Kusuma; Rizal Rizal (Journal of Mathematical and Fundamental Sciences, 2023)
This study was conducted in order to ascertain how green tea extract (GTE) could affect inflammatory markers, including level of interleukin-(IL)-12, IL-18 of serum and lung, tumor necrosis factor (TNF)-α, gene expression of NLR family-pyrin-domain containing 3 (NLRP3) of lung, nuclear factor kappa B (NF-κB), lung histopathology, and IL-6 expression of lung tissue in lipopolysaccharide (LPS)-treated rats as ARDS animal model. Rats were given GTE at dosages of 0, 50, 400, 800 mg/kg of body weight for 28 days to boost their immune systems. The rats were then stimulated with LPS (5 g/kg of BW) and after that continued to receive GTE for 28 days. Levels of serum or lung IL-18, IL-12, TNF-α, were measured using the ELISA method; expression of lung NF-κB and NLRP3 was measured by qRT-PCR; immunohistochemistry (IHC) was implemented to assess lung IL-6 expression; and lung histopathology was evaluated through the bleeding, inflammation, and alveolus scores. GTE had the ability to lower serum IL-18, lung TNF-α, and lung IL-12 levels; suppress the lung gene expression of NF-κB, NLRP-3, IL-6 expression; and improve lung histopathology. Green tea extract inhibited inflammation in the ARDS rat model by decreasing the proinflammatory cytokine level and proinflammatory gene expression.